Mechanical effects of foundation restoration on onlay preparations of mandibular first molars after endodontic treatment - Qiuyue Wang; Dongqi Shi; Xiangling Liu; Weijun Zhang; Zhaolun Sun; Yao Feng; Lingbo Zhang (BMC Oral Health)
Abstract Background Foundation restorations involve the use of materials such as composite resins to partially restore defective dentin structures. They can be used to simplify the geometry of complex cavities, facilitate restoration insertion, and reduce the polymerization shrinkage of the adhesive. However, the stress distribution of teeth restored after foundation restoration placement is not fully understood. Methods Finite element analysis was used in this study. The purpose was to analyze the stress distribution of onlays with composite resin foundation restorations and to investigate the potential benefits of preserving the remaining dental tissue.A three-dimensional finite element model of a mesial proximal defect of the mandibular first molar after endodontic treatment was established. Four types of onlay restorations (GA and GB: complete-coverage onlay; GC and GD: partial-coverage onlay) were designed using this model. After the models were established, a fixed vertical load of 600 N and an oblique load of 200 N were applied, and the stress distributions were compared between the monolithic ceramic block restorations (GA and GC) and those with foundation restorations (GB and GD). The stress distributions of the onlays and models were also analyzed. Results Under vertical loading conditions, GD exhibited higher peak equivalent stress levels in the onlay and adhesive layers. The maximum principal stress experienced by enamel was lower in GB and GD than in GA and GC, whereas it was greater in GB and GD than in GA and GC for the onlay and adhesive layer. Under oblique loading, the peak equivalent stress and maximum principal stress of the adhesive layer and enamel were the lowest in the GB and GD groups. Conclusions Foundation restorations provide good stress dispersion, which can improve the protection of the remaining dental tissue. However, onlay restorations after foundation restoration placement should be used with caution in patients with excessive occlusal forces. Oblique loading was more destructive to the adhesive layer and remaining dental tissue. Complete-coverage restorations have better stress dispersion than partial-coverage restorations.